MOSQUITO LARVICIDAL ACTIVITY OF COUMARIN (C29H42O8) ISOLATED FROM Eucalyptus deglupta LEAVES AND ITS MOLECULAR DOCKING STUDIES AGAINST Aedesaegypti L. AND Culex quinquefasciatus SAY. (DIPTERA: CULICIDAE) - RAJ, S. HANNAH CATHERINE; SHETTU, N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Several species of mosquitoes serve as the crucial vector of transmitting disease causing microbes to humans. In particular, Aedesaegypti transmits dengue fever, chikungunya fever, zika fever viruses and Culex quinquefasciatus transmits filariasisnematode. Mosquito control with plant isolated compounds would be more suitable to avoid the ill effects of chemical insecticides. In the present study, ethanol extract of Eucalyptus deglupta leaves weresubjected to column chromatography and isolated a compound and tested on Cx. quinquefasciatus and Ae. aegypti mosquito larvae and molecular docking analysis were performed to find the site of action.Based on the 1H NMR and 13C NMR spectrum, the isolated compound containing coumarin unit connected with tetrahydrofuran and fatty acid attached through ester linkages was confirmed. The presence of ester carbonyl, aromatic, polyol and aliphatic protons and carbons were also identified from 1H and 13C NMR spectrum. The active compound was identified as (3,4‐dihydroxy‐5‐{[(3,6,8‐trimethyl‐2‐oxo‐2H‐chromen‐7‐yl) oxy]methyl}oxolan‐2‐yl)methyl 3,7‐dimethylnonanoate (Mol.weight: 518.6 g/mol; Mol. Form.: C29H42O8). The isolated compound was found to be the most effective, which showed LC50 and LC90 values of 3.99ppm, 7.76ppm against Cx. quinquefasciatus and 4.99 ppm, 10.78 ppm against Ae. aegypti larvae, respectively. The docking studies recorded significant binding to the two-mosquito docking model. The results of the present study show that the compound can be used for controlling the larvae of Cx. quinquefasciatus and Ae. Aegypti mosquitoes.